MiR-146b-5p/TRAF6 axis is essential for Ginkgo biloba L. extract GBE to attenuate LPS-induced neuroinflammation - Liu, Min; Peng, Yulin; Che, Yilin; Zhou, Meirong; Bai, Ying; Tang, Wei; Huang, Shanshan; Zhang, Baojing; Deng, Sa; Wang, Chao; Yu, Zhenlong (Frontiers in Pharmacology, 2022)
Background: Neuroinflammation plays a crucial role in the pathogenesis and progression of various neurodegenerative diseases, including Alzheimer’s disease. The Ginkgo biloba leaf extract (GBE) has been widely used to treat cerebral and peripheral blood circulation disorders. However, its potential targets and underlying mechanisms regarding neuroinflammation have not yet been characterized. Aims: The purpose of this study was to investigate and validate the anti-neuroinflammatory properties of GBE against lipopolysaccharide (LPS)-mediated inflammation and to determine the underlying molecular mechanisms. Methods: The effect of GBE on LPS-induced release of inflammatory cytokines was examined using ELISA and western blot assay. The effects of GBE on NF-κB binding activity and translocation were determined via luciferase, streptavidin-agarose pulldown, and immunofluorescence assays. The potential targets of GBE were screened from the GEO and microRNA databases and further identified via qPCR, luciferase, gene mutation, and western blot assays. Results: GBE significantly inhibited LPS-induced pro-inflammatory responses in BV-2 and U87 cells, with no obvious cytotoxicity. GBE significantly induced miR-146b-5p expression, which negatively regulated TRAF6 expression by targeting its 3'-UTR. Thus, due to TRAF6 suppression, GBE decreases the transcriptional activity of NF-κB and the expression of pro-inflammatory cytokines, such as interleukin (IL)-1β, IL-6, tumor necrosis factor (TNF)-α, and cyclooxygenase (COX)-2, and finally reverses LPS-induced neuroinflammation. Conclusion: Our study revealed the anti-neuroinflammatory mechanism of GBE through the miR-146b-5p/TRAF6 axis and provided a theoretical basis for its rational clinical application.